2000
DOI: 10.1001/archsurg.135.8.948
|View full text |Cite
|
Sign up to set email alerts
|

Wound Recurrences Following Laparoscopic-Assisted Colectomy for Cancer

Abstract: To determine the incidence and clinical relevance of wound recurrences (WRs) following laparoscopic-assisted colectomy for cancer; to analyze the most recent experimental studies examining possible pathogenic mechanisms; and to delineate possible prevention strategies. Data Sources: A MEDLINE search was conducted using the words "colectomy," "laparoscopy," and "recurrence, local." Additional articles were retrieved by crossreferencing. Study Selection: All clinical and experimental studies retrieved were revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(39 citation statements)
references
References 112 publications
0
36
0
3
Order By: Relevance
“…It is believed that CO 2 promotes tumor cell growth, but in vitro studies have analyzed alterations caused by CO 2 in tumor growth and have demonstrated that it does not actually occur. The results suggest that CO 2 of at least 10 to 15 mmHg will cause a toxic effect 107 . Regarding the fact that videolaparoscopy may replace the conventional laparotomy access in the treatment of intra-abdominal tumors, the question remains very complex.…”
Section: Vol 32 Nºmentioning
confidence: 91%
See 1 more Smart Citation
“…It is believed that CO 2 promotes tumor cell growth, but in vitro studies have analyzed alterations caused by CO 2 in tumor growth and have demonstrated that it does not actually occur. The results suggest that CO 2 of at least 10 to 15 mmHg will cause a toxic effect 107 . Regarding the fact that videolaparoscopy may replace the conventional laparotomy access in the treatment of intra-abdominal tumors, the question remains very complex.…”
Section: Vol 32 Nºmentioning
confidence: 91%
“…Through a review on current literature and sources such as SCIELO and LILACS, we can conclude that the use of videolaparoscopy as a proper oncological technique remains controversial, especially because most studies in this area are retrospective and only suggest conclusions, without conditions to be adopted as a support to practices, and prospective randomized studies are required to monitor patients for long postoperative periods, attesting the occurrence or non-occurrence of higher incidence of recurrence at trocar incision sites and lesion recurrence [107][108][109][110][111] .…”
Section: Vol 32 Nºmentioning
confidence: 99%
“…A major problem that limits the broad acceptance of laparoscopic cancer surgeries is the significant skepti cism about LCS for cancer although laparoscopy is very popular in the treatment of many intra-abdominal disorders. The potential benefits of the laparoscopic technique must in fact be weighed against the potential for limited oncological outcomes due to inadequate resection, potential occurrence of port site metastases or metastatic spread [30][31][32] . Moreover, surgeons are fearful that laparoscopic surgery could be more harmful to cancer patients than open procedures [33] .…”
Section: Role Of Ltmementioning
confidence: 99%
“…Several case series, and even some registries, reported rates of trocar-site recurrences in excess of what was historically reported for open surgery. [78][79][80][81][82] This generated great interest in animal model investigations including mechanisms of tumor cell dissemination and immunologic studies. Clinical evidence was required to refute or confirm the association between the wound tumor implants and laparoscopic colectomy for cancer.…”
Section: Laparoscopic Resection For Colon Cancermentioning
confidence: 99%